Screening and evaluation of soil fungal isolates for xylanase production - Kulkarni, Pragya; Gupta, Nivedita (Recent Research in Science and Technology, 2013)
Fungi are well known for their ability to excrete enzyme into the environment for their growth and survival. 32 fungal strains isolated from soil of social forest area of Bhilai Township were screened for xylanase production. Out of the 17 primary positive xylanase strains showing clear zones around growing colony, 03 good producers were identified as Aspergillus niger (AS012), Gliocledium sp (GS005) and Trichoderma viride (TS007). Solid state fermentation conditions were found to support optimally over Liquid state condition and Aspergillus niger (AS012) was appeared as best producer among them. Further studies were carried out on Aspergillus niger to standardize best natural substrate for xylanase production under solid state fermentation condition. Wheat bran supported the best followed by whole oat powder and paddy straw respectively.